2021
DOI: 10.3389/fcell.2021.794475
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Omics Analysis of Cancer Cell Lines with High/Low Ferroptosis Scores and Development of a Ferroptosis-Related Model for Multiple Cancer Types

Abstract: Background: Ferroptosis is a newly identified regulated cell death characterized by iron-dependent lipid peroxidation and subsequent membrane oxidative damage, which has been implicated in multiple types of cancers. The multi-omics differences between cancer cell lines with high/low ferroptosis scores remain to be elucidated.Methods and Materials: We used RNA-seq gene expression, gene mutation, miRNA expression, metabolites, copy number variation, and drug sensitivity data of cancer cell lines from DEPMAP to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…Recent studies have confirmed that a variety of FDA-approved drugs, such as flubendazole [20], brequinar [6], and sulfasalazine [27], can play an antitumor role by inducing ferroptosis, indicating the feasibility of such drugs in combination with chemotherapy. Previous studies have shown that FINs can improve the sensitivity of a variety of chemotherapeutic drugs including docetaxel [28], cisplatin [29], and oxaliplatin [30]. A recent study has confirmed that FINs were found to significantly improve the efficacy of antiandrogenic drugs for PCa without increasing side effects [15].…”
Section: Discussionmentioning
confidence: 97%
“…Recent studies have confirmed that a variety of FDA-approved drugs, such as flubendazole [20], brequinar [6], and sulfasalazine [27], can play an antitumor role by inducing ferroptosis, indicating the feasibility of such drugs in combination with chemotherapy. Previous studies have shown that FINs can improve the sensitivity of a variety of chemotherapeutic drugs including docetaxel [28], cisplatin [29], and oxaliplatin [30]. A recent study has confirmed that FINs were found to significantly improve the efficacy of antiandrogenic drugs for PCa without increasing side effects [15].…”
Section: Discussionmentioning
confidence: 97%
“…Previous studies have analyzed ferroptosis-correlated signatures or genes in single-types of cancer, but we noted that a systematic landscape of associations among tumor ferroptosis, clinical outcomes, tumor microenvironment, and therapies in human cancers is lacking. Besides, recent studies have also analyzed ferroptosis-correlated molecular signatures and constructed scores for these cancer types (5)(6)(7). However, most of these studies analyzed ferroptosis signatures without distinguishing between drive and suppress regulators.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, since ferroptosis has been reported to be related to cancer immunity, activation of ferroptosis may serve as a new strategy for developing of anti-cancer agents with immunotherapeutic potential (4). Several recent studies have identified ferroptosis-correlated molecular signatures in multiple cancer types (5)(6)(7). Nevertheless, these studies used ferroptosis regulators without distinguishing between drive and suppress regulators.…”
Section: Introductionmentioning
confidence: 99%
“…Since various types of cancer have different sensitivities to ferroptosis, the choice of small molecule drugs needs to be further investigated. [ 57 ]…”
Section: Traditional Drugs Desiderate Improvements By Nanotechnologymentioning
confidence: 99%